Metode Bimbingan Imajinasi Rekaman Audiovisual Terhadap Stres Hospitalisasi Pada Anak Usia Sekolah - Khalida Ziah Sibualamu; Sri Resky Mustafa; Emmi Wahyuni (PT.Mantaya Idea Batara, 2021)
Objective: This study aims to determine The effect of the audiovisual recording imagination guidance method on hospitalization stress in school-age children at Bhayangkara Hospital Makassar. Methods: This study uses a quantitative design with a quasi-experimental method only post-test with control group design. Results: The results of the study using the Mann-Whitney test showed that there was a significant difference (p 0.022) between the audiovisual recording imagination guidance method group and the control group. Discussion: Providing imagination guidance on audio-visual recordings affects reducing hospitalization stress levels in school-age children (6-12 years). Conclusion: The audio-visual recording imagination guidance method is more influential in reducing hospitalization stress in school-age children. Suggestion: It is expected that pediatric nurses will be able to apply the audiovisual recording imagination guidance method to the school-age children with a nursing process approach.